Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) pada Mata Pelajaran IPAS Kelas VIII SMP - Salmanura, Fadhila; Hendri, Nofri (Al-DYAS, 2024)
Augmented Reality (AR) learning media is a new learning innovation that displays interesting 3D animation visuals and makes complex and abstract concepts more real so that it triggers students' interest and curiosity in learning, so it can be used as an alternative in learning problems. This study aims to develop learning media for IPAS Class VIII Junior High School in order to produce valid media that is practical and effective for use by teachers and students This type of research is a development research (Reseacrh an Development) with the 4D (Four-D) development model. The average score for media validity assessment using Likert scale percentage presentation with media assessment by validator I is 4.93 and the percentage of 98% is categorized as "very valid", validator II is 4.73 with a percentage of 94% categorized as "very valid". And the average score of the material validator is 4.79 with a percentage of 95% categorized as "very valid". The research was conducted in 4 stages, the first stage by conducting curriculum analysis, learner analysis, and concept analysis. Then the initial product development was carried out by making flowcharts and storyboards and then making learning media with the Aseemblr edu application. Furthermore, the validity test stage is carried out by media and material validators, the last one is conducting a practicality trial and effectiveness trial for VIII grade junior high school students.